2002
DOI: 10.1113/jphysiol.2002.027938
|View full text |Cite
|
Sign up to set email alerts
|

Motor fatigue and cognitive task performance in humans

Abstract: During fatiguing submaximal contractions a constant force production can be obtained at the cost of an increasing central command intensity. Little is known about the interaction between the underlying central mechanisms driving motor behaviour and cognitive functions. To address this issue, subjects performed four tasks: an auditory choice reaction task (CRT), a CRT simultaneously with a fatiguing or a non‐fatiguing submaximal muscle contraction task, and a fatiguing submaximal contraction task alone. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 20 publications
(19 reference statements)
9
118
2
3
Order By: Relevance
“…Our findings and complementary data from several studies, which showed that mental fatigue influences motor performance and action planning (Lorist et al, 2000(Lorist et al, , 2002Marcora et al, 2009), underline the interdependence of motor and cognitive states. Because mental training is consistently used, alone or in combination with physical training, in sports and motor rehabilitation, we consider that sport psychologists and therapists should take into consideration physical and/or mental fatigue in the elaboration of their training programs.…”
Section: Muscle Fatigue Alters the Temporal Features Of Actual And Mesupporting
confidence: 82%
“…Our findings and complementary data from several studies, which showed that mental fatigue influences motor performance and action planning (Lorist et al, 2000(Lorist et al, , 2002Marcora et al, 2009), underline the interdependence of motor and cognitive states. Because mental training is consistently used, alone or in combination with physical training, in sports and motor rehabilitation, we consider that sport psychologists and therapists should take into consideration physical and/or mental fatigue in the elaboration of their training programs.…”
Section: Muscle Fatigue Alters the Temporal Features Of Actual And Mesupporting
confidence: 82%
“…220 Chang-Hong Youm Tae-Hyeon Kim ․ 발생할 수 있는 능력이며 만약 발목 관절의 안정근이 충분한 , 힘을 생산할 수 없다면 발목 관절의 불안정으로 인해 자세 동 , 요는 증가하게 될 것이다 (Yaggie & McGregor, 2002 Lorist, Kernell, Meijman, & Zijdewind, 2002), 은 부분을 포함하고 있는 복잡한 현상이다 이러한 근육 피로는 근수축 효율성과 Boyas & Guevel, 2011). 고유감각 정보를 변경시키며 운동 협응과 자세제어에 영향을 미친다 근육의 피로로 인한 (Chabran, Maton, & Fourment, 2002).…”
unclassified
“…It is the consequence of motor task performed over a long period of time (Lorist et al, 2002). The causes of muscle fatigue are wide-ranging with complex interaction of peripheral and central mechanism.…”
Section: Introductionmentioning
confidence: 99%